Sustainable development indicators for electric power generation companies in Ecuador: A case study. (April 2023) - Martínez, Augusto Polibio; Jara-Alvear, José; Andrade, Rolando Josué; Icaza, Daniel
Abstract: The United Nations implemented the Sustainable Development Goals (SDGs) through an action plan consisting of 17 topics considered essential to achieve all the commitments made by the countries in the 2030 Agenda. This study evaluates SDG compliances by the electric power generation companies of Ecuador, focusing on the case of Corporación Eléctrica del Ecuador (CELEC EP). A comparative analysis of indicators used in recognized companies worldwide is carried out, and after an evaluation, it is determined that CELEC EP complies with 14 of the 26 approved indicators. Highlights: The Sustainable Development Goals are considered fundamental in Ecuador. The Ecuadorian electricity generation companies must align themselves based on the commitments assumed in the 2030 Agenda. The Sustainable Development Goals in the electric companies of Ecuador is evaluated, case study CELEC EP. A comparative analysis of indicators exposed worldwide and those of CELEC EP is carried out. It is determined that CELEC EP meets 14 of the 26 indicators.